The influence of large amplitude planetary waves on the Antarctic ozone hole of austral spring 2017 - Evtushevsky, O; Klekociuk, AR; Kravchenko, V; Milinevsky, G; Grytsai, A (Journal of Southern Hemisphere Earth Systems Science, 2020)
Quasi-stationary planetary wave activity in the lowerAntarctic stratosphere in the late austral winter was animportant contributor to the preconditioning of the ozonehole in spring 2017. Observations show that the ozonehole area in spring 2017 was at the level of 1980s, i.e.almost half the maximum size in 2000s. The observedozone hole area was close to that forecasted based on aleast-squares linear regression between wave amplitude inAugust and ozone hole area in SeptemberNovember. Weshow that the key factor which contributed to thepreconditioning of the Antarctic stratosphere for arelatively small ozone hole in the spring of 2017 was thedevelopment of large-amplitude stratospheric planetarywaves of zonal wavenumbers 1 and 2 in late winter. Thewaves likely originated from tropospheric wave trains, andpromoted the development of strong mid-latitudeanticyclones in the lower stratosphere which interactedwith the stratospheric polar vortex and strongly eroded thevortex in August and September, mitigating the overalllevel of ozone loss.